Fabrication of membranes using sol-gel chemistry on glass chips and protein separations using on-column fluorescence labeling by capillary electrophoresis - Cao, Yueping (Kansas State University, 2007)
The field of microfluidic devices has being developed quickly. It is aimed at integration of many chemical functions in a single chip, such as sample pretreatment, preconcentration, separation and detection, which provides a number of advantages including simplicity, automation, reduced analysis time, decrease in amount of samples and reduced formation of waste. Its potential applications have been conducted in the fields such as biotechnology, pharmaceuticals, life sciences, public health, agriculture and related areas. Membrane technology has been applied in analytical chemistry for many years and has won substantial growth in microfluidics over the past 10 years. Membrane is used to control transfer of some kinds of species, which can be employed for sample concentration, sample preparation, sample filtration and microreactors and so on. Sol-gel process, which usually involves catalytic hydrolysis of sol-gel precursor(s) and catalytic polycondensation of the hydrolyzed products and other sol-gel-active components present in the reaction medium to form a macromolecular network structure, is one of the most suitable methods for membrane fabrication. In this work, titanium membrane was fabricated inside glass microchips using the precursor of titanium isopropoxide. The resulted membranes demonstrated the excellent preconcentration effect. Followed separation and detection were also achieved. CE has been highly accepted as an efficient separation technique for qualitative and quantitative determination, which is performed using a narrow-bore capillary tube. It offers advantages of simplicity, high resolution separation, and minimal cost in terms of analysis time and sample consumption. In this work, protein separations were carried out by CE. Laser-induced fluorescence was used as detection. On-column fluorescence labeling using a fluorogenic labeling reagent was made. Under suitable experimental conditions, an excellent separation performance with about 1.4 million theoretical plate numbers was achieved.
Keywords: Membrane; Sol-gel chemistry; Microfluidic device; Capillary electrophoresis; Chemistry, Analytical (0486)